A semantic web-based approach for enhancing oral history management systems / Ahmad Zam Hariro Samsudin, Shah Jahan Miah and Michael McGrath - Samsudin, Ahmad Zam Hariro; Miah, Shah Jahan; McGrath, Michael (Faculty of Information Management, 2013)
Semantic web (SW) technologies have become one of the well-accepted tools for enhancing web application usages. However, this technology has not been still immature for the enhancement of knowledge management (KM) system susages. This paper reports an investigation on current issues of a KM system, so-called Oral History Management Systems (OHMS) and benefits of SW over the issues. The study first conduct interviews to identify issues and benefits of the current applications in parallel to a literature survey that finds potential benefits and issues of SW technologies. The initial outcomes are then used to develop both frameworks of current OHMS and preferred SW based in order to compare for achieving the betterment of OHMS usages in the targeted problem context, specially for enhancing decision making provisions. In this paper, we summarize the entire research project highlighting not just a conceptual and theoretical issue, but also for the enhancement of practical usages of OHMS across the Universities in Malaysia.